Experimental research of a high efficiency natural convection double-flow solar air heater - Quiñonez Choquecota, José (2019)
The design, construction and evaluation of a parallel dual-flow air heater solar collector that has the V-shaped corrugated absorbent plate and that works by natural convection is presented. The collector has been evaluated for clear sky when installed on a vertical wall in the city of Puno, oriented towards the geographical north in the autumn season. The performance parameters allowed to obtain high efficiency and the construction is low cost. The maximum outlet air temperature of the collector reached 95,7 ºC for a solar intensity of 758 W/m2, and the average mass flow for sunny days was 0,0094 kg/s, in addition it was found that the mass flow is very sensitive to air velocity and density. The average efficiency of the collector is 51,1% which represents a good performance since it extracts a large amount of completely passive thermal energy without requiring additional external energy. The designed collector is respectful with the environment and is designed to meet the energy demands in frigid regions, it can operate more efficiently in the autumn and winter periods because it has a higher incidence angle at this time.